Human Adjustment to Technological Change : An Economist’s View - Kruger, Arthur (Relations industrielles / Industrial Relations, 1971)
The focus of this paper is to examine how collective bargaining has attempted to cope with the problems of worker displacement and how these developments might indicate future trends in union-management relations as well as the limitations of collective bargaining.